Corn agronomic characteristics according to crop year, spacing and plant population densities - Buso, Wilian Henrique Diniz; Silva, Luciana Borges e; Rios, Anderli Divina Ferreira; Firmiano, Raquel Silva (Comunicata Scientiae, 2016)
The present study aimed to evaluate the influence of row spacing, plant density, crop year and yield in crop agronomic parameters in a ‘Cerrado’ area in Brazil. The experiments were conducted during the 2010/2011 and 2011/2012 crop years, at an experimental Farm of the IF Goiás Campus Ceres, located in the city of Ceres, Goiás, Brazil. The experiment was conducted in a complete randomized block design in a 2x3x2 factorial (two crop years: 2010/2011 and 2011/2012, three population densities: 60,000, 70,000 and 80,000 plants ha-1 and two spacing: 0.50 and 0.80 m) with four repetitions, totaling 48 plots. The observed values for plant height and cob height were higher for the 2011/2012 season with values of 2.56 and 1.26 m, respectively. The cob diameter was higher for the 2011/2012 crop year with a value of 51.92 mm. The yield was higher for the 2010/2011 harvest. Increasing plant population and reducing row spacing can lead to an increase on the grain yield due to better spatial distribution of plants per area, fact observed mainly during the 2010/2011 crop year. Corn maintains high productivity with spacing of 0.50 and 0.80m. Increases in plant density can lead to increase on yield. Increasing plant population reduced the corn stem diameter.